N-(2-Hydroxypropyl)methacrylamide-based polymer conjugates with pH-controlled activation of doxorubicin for cell-specific or passive tumour targeting. Synthesis by RAFT polymerisation and physicochemical characterisation - Chytil, Petr; Etrych, Tomáš; Kříž, Jaroslav; Šubr, Vladimír; Ulbrich, Karel (European journal of pharmaceutical sciences, 2010)
Controlled radical reversible addition-fragmentation chain transfer (RAFT) polymerisation was used to prepare water-soluble polymer-drug carriers based on copolymers of N-(2-hydroxypropyl)methacrylamide (HPMA) with a hydrazide group-containing monomer, showing well-defined structure with narrow molecular weight distribution (approx. 1.1-1.2). The anticancer therapeutic doxorubicin was bound to the polymeric carrier by a hydrazone bond, enabling pH-controlled release under mildly acid conditions that mimics the environment in endosomes/lysosomes of tumour cells. RAFT polymerisation facilitated the synthesis of semitelechelic copolymers, which were used in the synthesis of monoclonal anti-CD20 antibody-polymer-drug conjugate designed for cell-specific tumour targeting. They were also used for producing a biodegradable high-molecular-weight graft polymer-drug conjugate that degrade in the presence of glutathione, which is designed for passive targeting to solid tumours. The conjugates exhibited well-defined structures with narrow molecular weight distributions of approx. 1.3 and pH-controlled drug release.
Keywords: Drug Carriers; doxorubicin; Antibodies, Monoclonal; Doxorubicin; Drug Delivery Systems; polymerizace; molekulární struktura; Polymerization; Molecular Structure; Acrylamides; akrylamidy; Kinetics; kinetika; lékové transportní systémy; Hydrogen-Ion Concentration; nosiče léků; monoklonální protilátky; koncentrace vodíkových iontů; Antibiotics, Antineoplastic; protinádorová antibiotika